2006
DOI: 10.1007/bf03194650
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of alpha-thalassemia in microcytic hypochromic anemia patients from North India

Abstract: Microcytic hypochromic anemia is a common condition in clinical practice and alpha-thalassemia has to be considered as a differential diagnosis. Molecular diagnosis of alpha-thalassemia is possible by polymerase chain reaction. The aim of this study was to evaluate the frequency of alpha-gene numbers in subjects with microcytosis. In total, 276 subjects with microcytic hypochromic anemia [MCV<80fl; MCH<27pg] were studied. These include 125 with thalassemia trait, 48 with thalassemia major, 26 with sickle-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…This was previously reported [14], where alpha thalassemia trait patients were characterized by slight reduction in haemoglobin level. The MCV and MCH showed microcytosis and hypochromasia in adults, and this finding is consistent with many previous studies concerning the contribution of alpha thalassemia to microcytosis and hypochromia [20][21][22][23][24][25][26][27], while others [14,28] reported slight microcytosis and hypochromasia or sometimes normal with alpha thalassemia trait. Unlike many other similar studies that have examined the red cell indices in alpha thalassaemia, present cohort showed significantly lower MCV (52-53 fL) giving an impression of additional pathology.…”
Section: Discussionsupporting
confidence: 92%
“…This was previously reported [14], where alpha thalassemia trait patients were characterized by slight reduction in haemoglobin level. The MCV and MCH showed microcytosis and hypochromasia in adults, and this finding is consistent with many previous studies concerning the contribution of alpha thalassemia to microcytosis and hypochromia [20][21][22][23][24][25][26][27], while others [14,28] reported slight microcytosis and hypochromasia or sometimes normal with alpha thalassemia trait. Unlike many other similar studies that have examined the red cell indices in alpha thalassaemia, present cohort showed significantly lower MCV (52-53 fL) giving an impression of additional pathology.…”
Section: Discussionsupporting
confidence: 92%
“…This was previously reported (14) , where alpha thalassemia trait patients were characterized by slight reduction in haemoglobin level. The MCV and MCH showed microcytosis and hypochromasia in adults, and this finding is consistent with many previous studies concerning the contribution of alpha thalassemia to microcytosis and hypochromia (20,22,23,24,25,26,27,28) , while others (14,21) reported slight microcytosis and hypochromasia or sometimes normal with alpha thalassemia trait. Unlike many other similar studies that have examined the red cell indices in alpha thalassaemia, present cohort showed significantly lower MCV (52-53fL) giving an impression of additional pathology.…”
Section: Methodssupporting
confidence: 92%
“…reported a study of 276 cases, and found that 33 of these individuals had –α 3.7 deletions (12%), seven of them with concurrent SS/Sβ-thalassemia [19]. Similar results were published by Nava et al ., who found –α 3.7 deletions to be the most common mutations in the α-globin chain, and observed –α 3.7 deletion and anti-3.7 gene triplication with the presence of the sickle cell trait in 17 and in three cases respectively [20].…”
Section: Discussionsupporting
confidence: 74%